Antioxidant Responses in Copepods Are Driven Primarily by Food Intake, Not by Toxin-Producing Cyanobacteria in the Diet - Gorokhova, Elena; El-Shehawy, Rehab (Frontiers in Physiology, 2022)
The association between oxidative processes and physiological responses has received much attention in ecotoxicity assessment. In the Baltic Sea, bloom-forming cyanobacterium Nodularia spumigena is a significant producer of various bioactive compounds, and both positive and adverse effects on grazers feeding in cyanobacteria blooms are reported. To elucidate the effect mechanisms and species sensitivity to the cyanobacteria-dominating diet, we exposed two Baltic copepods, Acartia bifilosa and Eurytemora affinis, to a diet consisting of toxin-producing cyanobacteria N. spumigena and a high-quality food Rhodomonas salina at 0 to 300 μg C L-1; the control food was Rhodomonas salina provided as a monodiet at the same food levels. The subcellular responses to food type and availability were assayed using a suite of biomarkers – antioxidant enzymes [superoxide dismutases (SOD), catalase (CAT), and glutathione S-transferases (GST)] and acetylcholinesterase (AChE). In parallel, we measured feeding activity using gut content (GC) assayed by real-time PCR analysis that quantified amounts of the prey DNA in copepod stomachs. As growth and reproduction endpoints, individual RNA content (a proxy for protein synthesis capacity), egg production rate (EPR), and egg viability (EV%) were used. In both toxic and nontoxic foods, copepod GC, RNA content, and EPR increased with food availability. Antioxidant enzyme activities increased with food availability regardless of the diet type. Moreover, CAT (both copepods), SOD, and GST (A. bifilosa) were upregulated in the copepods receiving cyanobacteria; the response was detectable when adjusted for the feeding and/or growth responses. By contrast, the diet effects were not significant when food concentration was used as a co-variable. A bimodal response in AChE was observed in A. bifilosa feeding on cyanobacteria, with up to 52% increase at the lower levels (5-25 μg C L-1) and a 32% inhibition at the highest food concentrations. These findings contribute to the refinement of biomarker use for assessing environmental stress and mechanistic understanding of cyanobacteria effects in grazers. They also suggest that antioxidant and AChE responses to feeding activity and diet should be accounted for when using biomarker profiles in field-collected animals in the Baltic Sea and, perhaps other systems, where toxic cyanobacteria are common.